Inflammasomes and idiopathic inflammatory myopathies - Sun, Rui; Chu, Jiyan; Li, Ping (Frontiers in Immunology, 2024)
Idiopathic inflammatory myopathies (IIM) are a group of systemic autoimmune diseases characterized by muscle weakness and elevated serum creatine kinase levels. Recent research has highlighted the role of the innate immune system, particularly inflammasomes, in the pathogenesis of IIM. This review focuses on the role of inflammasomes, specifically NLRP3 and AIM2, and their associated proteins in the development of IIM. We discuss the molecular mechanisms of pyroptosis, a programmed cell death pathway that triggers inflammation, and its association with IIM. The NLRP3 inflammasome, in particular, has been implicated in muscle fiber necrosis and the subsequent release of damage-associated molecular patterns (DAMPs), leading to inflammation. We also explore the potential therapeutic implications of targeting the NLRP3 inflammasome with inhibitors such as glyburide and MCC950, which have shown promise in reducing inflammation and improving muscle function in preclinical models. Additionally, we discuss the role of caspases, particularly caspase-1, in the canonical pyroptotic pathway associated with IIM. The understanding of these mechanisms offers new avenues for therapeutic intervention and a better comprehension of IIM pathophysiology.